Effect of Faricimab versus Aflibercept on Hyperreflective Foci in Patients with Diabetic Macular Edema from the YOSEMITE/RHINE Trials - Usha Chakravarthy, FRCOphth, PhD; Varun Chaudhary, MD, FRCS(C); Srinivas R. Sadda, MD; Colin S. Tan, FRCOphth, FRCSEd (Ophth); Stela Vujosevic, MD, PhD; Sascha Fauser, MD; Kara Gibson, PhD; Carl Glittenberg, MD; Nancy Holekamp, MD, FASRS; Ben Lanza, PhD; Andreas Maunz, PhD; Jeffrey R. Willis, MD, PhD; et al. (Ophthalmology Science)
Purpose: To compare the effect of faricimab, a dual angiopoietin-2 (Ang-2) and VEGF-A inhibitor, with aflibercept on resolution of hyperreflective foci (HRF) in patients with diabetic macular edema (DME). Design: A post hoc analysis of the randomized, double-masked, noninferiority YOSEMITE/RHINE (NCT03622580/NCT03622593) phase III trials. Participants: Adults with vision loss due to center-involving DME. Methods: A deep learning–based algorithm was used to automatically quantify HRF in spectral-domain OCT volume scans from YOSEMITE/RHINE. Study eyes were randomized to faricimab 6.0 mg every 8 weeks (Q8W; n = 519), faricimab 6.0 mg according to a personalized treat-and-extend (T&E)–based regimen (n = 524), and aflibercept 2.0 mg Q8W (n = 502). Hyperreflective foci were defined as hyperreflective objects up to 50 μm in diameter and assessed within the 1.0-mm and 3.0-mm–diameter ETDRS rings and by location within the inner and outer retina. Main Outcome Measures: Hyperreflective foci volume and count at baseline and over time through week 48 in the inner, outer, and total retina, 1-mm and 3-mm diameters; time to absence of HRF at 2 consecutive visits in the inner and outer retina, 1-mm diameter over 48 weeks. Results: Adjusted mean HRF volumes at week 48 were lower for faricimab Q8W (104.1 picoliter [pL]) and faricimab T&E (110.1 pL) compared with aflibercept (180.3 pL; nominal P < 0.001 for both) in the inner retina, 1-mm diameter. In the inner retina, 3-mm diameter adjusted mean HRF volumes at week 48 were lower for faricimab Q8W (763.9 pL) and faricimab T&E (777.2 pL) compared with aflibercept (1030.6 pL; nominal P < 0.001 for both). Similar results were obtained for volumes in the outer retina and for HRF counts. In the inner retina, 1-mm diameter, the 25th percentile for time to absence of HRF count at 2 consecutive visits was achieved 8 weeks earlier with faricimab Q8W and faricimab T&E versus aflibercept. Conclusions: Greater HRF reductions were achieved with faricimab versus aflibercept, supporting the therapeutic potential of dual Ang-2/VEGF-A inhibition to suppress disease activity in DME. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.